Impact of Credit Access on Charcoal Productivity: Implication for Sustainable Development, Oyo- State - F. I, Olagunju; I. K, Ojedokun; F, Ogunwole–Olapade (Asian Journal of Agriculture and Rural Development, 2013)
The impact of credit on charcoal productivity was assessed in Oyo state of southwestern Nigeria. Multi-stage sampling method was used to select 140 respondents. Data used in this study were gathered from traditional charcoal producers that have access and no access to credit with the aid of interview schedule; the analytical techniques used were descriptive statistics, Logit and multiple regression models. It was revealed that about 20% of the charcoal producers used loans from co-operative societies while 55% sourced their funds from personal savings. The model has a sigma square (σ2) value of 42.741 P<0.01which is an indication of a good fit and a normal distribution of the error term. About 50% of the charcoal farmers had limited access to formal funds due to insufficient collateral securities and this had negative effect on their business hence they recorded low level of farm income. The coefficient of these variables, years of experience in charcoal production, level of education, sources of credit, sources of log and their quantities were positively significant at 5% level. The multiple regression analysis revealed that frequency of extension visit, household size, amount and source of credit had a significant direct relationship with charcoal productivity. The study therefore concludes that credit acquisition by the charcoal producers had a significant impact on the charcoal productivity which brings about a sustainable development in the study area.